Study of high strength wheat flours considering their physicochemical and rheological characterisation as well as fermentation capacity using SW-NIR imaging. (March 2015) - Verdú, Samuel; Ivorra, Eugenio; Sánchez, Antonio J.; Barat, José M.; Grau, Raúl
Abstract: Characterisation of wheat flour destined for the bread-making process was studied by using hyperspectral image analyses based on Short-wave NIR imaging (SW-NIR). The first step was to characterise wheat flour batches by considering physicochemical, rheological and fermentation kinetic parameters. The second step was to capture the hyperspectral images of each batch. The results showed some significant differences in fermentation capacity in relation to gluten and its protein sub fractions. However, no significant rheological differences were observed. The acquired images were firstly analysed by principal component analysis, where a clustering tendency was observed. Then linear correlation maps were done to study the relationship between the SW-NIR spectra response and the physicochemical, rheological and fermentation kinetic parameters. The results showed an important correlation between the SW-NIR spectra (760–900 nm) and the fermentation capacity parameters of the batches, as well as gluten and its sub fraction proteins. The SW-NIR imaging analysis enabled to obtain useful information about wheat flour behaviour related to the fermentation process. Thus the studied technique may represent a useful, rapid non-destructive method to help characterise wheat flours with non-different rheological parameters by considering their behaviour during the fermentation process. Highlights: Link of NIR imaging method to chemical and fermentation kinetic parameters of flour. Differences between six different wheat flour batches were analysed. Differences in the fermentation behaviour were observed. Information obtained by technique is able to characterise flour properties.